Perceptions of the First-Line Supervisor's Authority: A Study in Superior-Subordinate Communication - Boyd, Bradford B.; Jensen, Jane (Academy of Management Journal, 1972)
This study attempts to determine whether differences exist in the perception of the first-level manager's authority as seen by the first-level manager and his immediate superior. It also attempts to relate the differences that are observed to some general factors which might suggest variables or obstacles that inhibit the communication process.